Interrogating secularism : race and religion in Arab transnational literature and art - Haque, Danielle (Critical Arab American studies., 2019)
Interrogating Secularism is a call to rethink binary categories of "religion" and "secularism" in contemporary Arab American fiction and art. While most studies that explore the traffic between literature and issues of secularism emphasize how canonical texts naturalize and reinforce secular values, Interrogating Secularism approaches this nexus through novels written by and about ethnic and religious minorities. Haque juxtaposes accounts of secular experience in the writing of Arab Anglophone authors such as Mohja Kahf, Rabih Alameddine, Khaled Mattawa, Laila Lalami, and Rawi Hage, with Arab and Muslim artists such as Ninar Esber, Mounir Fatmi, Hasan Elahi, and Emily Jacir. Looking at multiple genres and modes of aesthetic production, including AIDS narratives, visual art, and digital media, Haque explores how their conventions are used to subvert the ideals tied to secularism and the various anxieties and investments that support secularism as a premise. These authors and artists critique Western iterations of secular thought in spaces such as art exhibits, airports, borders, and literary discourses to capture how the secularism thesis reproduces the exclusivity it intends to remedy.